Financing the Mobility of Students in European Higher Education - Salome Gvetadze (European Investment Fund (EIF), 2014)
This working paper provides an overview of the importance and tendencies of financing higher education and students' mobility. The analysis investigates problems stemming from unequal access to financing of education and mobility associated costs. It underlines the necessity of public help to correct market failures. It also shows that the establishment of an EU Student Loan Facility for cross-border mobility as a policy measure on EU level would have added value in order to contribute to the objective to increase the mobility of higher education students...
Keywords: 330